(untitled) (Journal of the College of Basic Education, 2022)
Egypt’s history is replete with a lot of events and influential figures in history, and the most prominent figure that has had a big role in Egypt is Queen Nazli, Queen shattered love, was manipulating Bokdar and her son Farouk through her actions childish shameful that were Taatsrvha despite attained great age group, but they did not heed the warnings and did not hesitate to achieve the purpose of riding roughshod over all the customs and traditions of modesty and social and political developments and the status and thus lost themselves first and then close them after that.